PENGARUH PAD, PMDN DAN ANGGARAN PENDIDIKAN TERHADAP PDRB DAN TINGKAT KEMISKINAN PADA KABUPATEN/KOTA DI PROVINSI KALIMANTAN BARAT - Aloisius; Meiran Panggabean (Department of Management - Institut Shanti Bhuana, 2023)
ABSTRACT This study aims to examine and analyze the effect of Regional Original Income (ROI), Domestic Investment (DI) and Education Budget on Gross Regional Domestic Product (GRDP) and Poverty, both partially and simultaneously. The data used is secondary data in the form of combined panel data from 12 regencies/cities in West Kalimantan Province in 2015-2020 which originate from the Central Bureau of Statistics and Regional Education Balance. This data is analyzed using path analysis (path analysis). The results showed that ROI had a positive and significant effect on GRDP, DI had a positive and significant effect on GRDP, the education budget had a positive but not significant effect on GRDP. ROI and DI have a negative and insignificant effect on the poverty rate, while the education budget has a negative and significant effect on the poverty rate in districts/cities in West Kalimantan Province.